Antifungal Activity of Cinnamon Oil against Macrophominaphaseolina by Poisoned Food Technique (International Journal of Food and Nutritional Sciences, 2022)
Macrophominaphaseolina is a devastating soil-borne fungal pathogen that causes severe diseases in various crops, leading to significant economic losses worldwide. With the growing concern over the indiscriminate use of synthetic fungicides and their adverse effects on the environment and human health, there is a pressing need to explore alternative and sustainable approaches for controlling fungal pathogens. This research paper investigates the antifungal potential of cinnamon oil against M. phaseolina using the Poisoned Food Technique. The study employed different concentrations of cinnamon oil viz., 20%, 40%, 60%, 80% and 100% to determine its inhibitory effect on fungal growth and development. The findings reveal that cinnamon oil exhibits significant antifungal activity against Macrophominaphaseolina, with higher concentrations resulting in greater inhibition. These results suggest that cinnamon oil holds promise as a potential natural fungicide for managing M. phaseolina and could contribute to the development of eco-friendly and sustainable disease management strategies in agriculture.